A Halocin Promotes DNA Uptake in Haloferax mediterranei - Chen, Shaoxing; Sun, Siqi; Korfanty, Gregory A.; Liu, Jingwen; Xiang, Hua (Frontiers in Microbiology, 2019)
Halocins are antimicrobial peptides or proteins that are produced by halophilic archaea. Although their function in inhibiting the growth of closely related haloarchaeal strains is well known, other physiological functions of halocins have also been proposed in recent years. To unveil the possible function and mechanism of halocins in DNA uptake, the halocin H4 producing strain Haloferax mediterranei DF50-ΔEPS (incapable of EPS production) was used in this study. We found that deletion of the halH4 resulted in the strain DF50-ΔEPSΔhalH4 which exhibited loss of natural DNA uptake ability. Moreover, supernatants of the halocin producing strain were capable of inducing the ability to uptake DNA. Obviously, halocin is likely responsible for inducing DNA uptake. Cell surface ultrastructures of these strains were varied from strains DF50-ΔEPS to DF50-ΔEPSΔhalH4. The cell surface of strain DF50-ΔEPS was rough due to numerous pinholes, while that of the strain DF50-ΔEPSΔhalH4 was smooth without visible pinholes. The morphology of the halH4 complemented strain, DF50-ΔEPSΔhalH4::H4, showed an intermediate phenotype between strains DF50-ΔEPS and DF50-ΔEPSΔhalH4. We speculate that halocin H4 may accelerate DNA uptake by perforating the cell surface ultrastructure. The halocin H4 may represent a novel inducer or activator of DNA uptake in Hfx. mediterranei.